Achieving Partial Nitrification-Anammox Process Dependent on Microalgal-Bacterial Consortia in a Photosequencing Batch Reactor - Yang, Miao; Xie, Kun-Peng; Ma, Chi; Yu, Si-Hui; Ma, Jing-Yi; Yu, Ze-Quan; Chen, Xi; Gong, Zheng (Frontiers in Bioengineering and Biotechnology, 2022)
Partial nitrification coupled with anammox process (PN/A) is an energy-efficient approach for nitrogen removal from low C/N wastewaters. In this study, PN/A was achieved with optimal oxygen supply from a green microalga, Chlorella sorokiniana. PN process was first initiated within 35 d, and the following algae-intensified PN then reached steady state within the next 32 d. The dissolved oxygen (DO) concentration gradually maintained at 0.6 mg L-1 via adjusting the photoperiod to be 6 h-light /18 h-dark, when the accumulation ratio of NO2--N and the removal ratio of NH4+-N were both more than 90%. The nitrogen removal capability of anammox was acclimated via elevating the individual effluent NH4+-N and NO2--N levels from 100, to 200, to 300 mg L-1. After acclimation, the removal rates of NH4+-N and total nitrogen (TN) reached over 70% and 80%, respectively, and almost all the NO2--N was removed. Then, the algae-intensified PN/A, algammox biofilm system, was successfully started up. When the NH4+-N level increased from 100 to 300 mg L-1, the TN removal varied between 78% and 82%. In the photosequencing bioreactor, C. sorokiniana, ammonia-oxidizing bacteria (AOB) and anammox coexisted with an illumination of 200 μmol m-2 s-1 and a 6 h-light /18 h-dark cycle. The DO levels ranged between 0.4 and 0.5 mg L-1. In addition, microbial community analysis by Illumina MiSeq sequencing showed that the dominant functional bacteria in the algae-intensified PN/A reactors included Nitrosomonas (AOB) and Candidatus Brocadia (anammox), while Nitrospira and Nitrobacter (nitrite oxidizing bacteria), together with Denitratisoma (denitrifier) were largely inhibited. Further studies are required to optimize the microalgal-bacterial consortia system to achieve superior nitrogen removal rates under controllable conditions.